Intraplaque Enhancement Is Associated With Artery-to-Artery Embolism in Symptomatic Vertebrobasilar Atherosclerotic Diseases - Hou, Zhikai; Li, Mingyao; Lyu, Jinhao; Xu, Ziqi; Liu, Yifan; He, Jianfeng; Jing, Jing; Wang, Rong; Wang, Yongjun; Lou, Xin; Miao, Zhongrong; Ma, Ning (Frontiers in Neurology, 2021)
Abstract Objective We try to compare whether the plaque characteristics and baseline features are different in patients with A-to-A (Artery-to-Artery) embolism and those with parent artery disease in the intracranial vertebrobasilar atherosclerotic disease. Methods From September 2014 to January 2017, patients with recent posterior circulation stroke due to intracranial vertebrobasilar atherosclerotic disease were analyzed. The plaque characteristics, including intraplaque compositions (intraplaque hemorrhage and intraplaque calcification), intraplaque enhancement, and remodeling index, were evaluated by using 3T high-resolution magnetic resonance imaging (HRMRI). The baseline features including vascular risk factors and the involved artery were collected. Patients were divided into A-to-A embolism and parent artery disease groups based on the diffusion-weighted images, T2-weighted images, or computed tomography. The plaque characteristics and baseline features were compared between the two groups. Results Among consecutive 298 patients, 51 patients were enrolled. 29 patients were A-to-A embolism and 22 patients were parent artery disease. Compared with parent artery disease, the occurrence rates of intraplaque enhancement and intracranial vertebral involvement were higher in the A-to-A embolism group (79.3% versus 36.4%; p=0.002 and 62.1% versus 18.2%; p=0.002, respectively). Multivariable logistic regression analysis showed intraplaque enhancement and intracranial vertebral artery plaques were also associated with A-to-A embolism. (adjusted OR, 7.31; 95%CI, 1.58-33.77; p=0.011 and adjusted OR, 9.42; 95%CI, 1.91-46.50; p=0.006, respectively). Conclusion Intraplaque enhancement and intracranial vertebral artery plaques seem to be more closely associated with A-to-A embolism than parent artery disease in patients with symptomatic intracranial vertebrobasilar disease.